The independent association of non‐alcoholic fatty liver disease with lower urinary tract symptoms/benign prostatic hyperplasia and erectile function scores. (18th April 2019) - Eren, Huseyin; Horsanali, Mustafa O.
Abstract : Objectives: To evaluate the association between non‐alcoholic fatty liver disease (NAFLD) and lower urinary tract symptoms (LUTS)/benign prostate hyperplasia (BPH) and erectile function. Patients and methods: In all, 356 men diagnosed with LUTS/BPH were evaluated retrospectively between January 2016 and March 2018. Anthropometric and laboratory data were collected. According to the liver echogenicity degree, patients were divided into four NAFLD groups: Grade 0 was considered as normal with no NAFLD, whilst Grades 1–3 NAFLD had increasing fat deposits. LUTS symptoms, prostate‐specific antigen (PSA) levels, prostate volumes (PVs), and five‐item version of the International Index of Erectile Function (IIEF‐5) scores were compared statistically between the NAFLD grades. Results: PSA levels did not differ between the groups. The International Prostate Symptom Score (IPSS), PV and post‐voided residual urine volume (PVR) were significantly greater in men with higher NAFLD grades. Conversely, the maximum urinary flow rate (Qmax ) and IIEF‐5 score were lower in men with higher NAFLD grades. The NAFLD grade, rather than being metabolic syndrome (MetS) positive, affected prostate parameters and IIEF‐5 scores. NAFLD grade correlated positively with IPSS, PV and PVR, whereas there was a negative correlation with Qmax and IIEF‐5 score. Age and NAFLD were independent predictors of IPSS, PV, Qmax, and PVR on multivariate analysis. Conclusion: We found that NAFLD was an independent predictive factor for IPSS, PV, Qmax, PVR and IIEF‐5 score. MetS was only a significant predictive factor for IIEF‐5 score, thus NAFLD may identify patients at high risk of LUTS better than MetS.